Analisis Efektivitas Manajemen Risiko Valuta Asing terhadap Profitabilitas PT Garuda Indonesia (Persero) Tbk (2020-2024) - Meilanie Tri Pratiwi; Asep Saepuloh; Muhamad Dzikry Raynan; Perwito Perwito (Indo Publishing, 2026)
The development of international capital flows has driven an increase in corporate involvement in cross-border transactions using foreign currencies, thereby creating exchange rate fluctuation risks. PT Garuda Indonesia (Persero) Tbk, as an airline company operating internationally, has a high level of foreign exchange exposure, particularly in operational costs and liabilities dominated by the US dollar. This study aims to analyze the effectiveness of foreign exchange risk management on the profitability of PT Garuda Indonesia (Persero) Tbk during the 2020–2024 period. The study uses a descriptive quantitative approach with secondary data sourced from the Bank Indonesia middle exchange rate and PT Garuda Indonesia (Persero) Tbk's annual reports. Foreign exchange risk is measured through the ratio of exchange rate gains (losses) to operating profit, while profitability is measured using Return on Assets (ROA). Research results show that the foreign exchange risk faced by companies is significant and impacts financial performance. The effectiveness of foreign exchange risk management shows varying results from year to year. Company profitability, measured using ROA, also experiences fluctuations. Descriptively, there is a correlation between the effectiveness of foreign exchange risk management and company profitability, although profitability is also influenced by factors other than exchange rate risk.